The Difference in the Effect of Progressive Muscle Relaxation and Elderly Exercise on Blood Pressure Reduction in Elderly Hypertensive Patients - Jati, Angling Krismaya; Utomo, Budi; Sukadarwanto, Sukadarwanto (Poltekkes Kemenkes Surakarta, 2023)
Background: Hypertension in the elderly isolated systolic hypertension (ISH), where increased systolic pressure increases the likelihood of stroke and myocardial infarction even if diastolic pressure is within normal limits. The purpose of this study was to determine the difference in the effect of progressive muscle relaxation and elderly exercise on blood pressure reduction in elderly hypertensive patients. Methods: This study used a two-group pre-test and post-test design involving 20 subjects randomly divided into two groups. Group I was given progressive muscle relaxation treatment, and group II was given elderly exercise treatment. The frequency of exercise was twice a week for two weeks. The measuring instrument used in this study was a sphygmomanometer. Results: Hypothesis I test using a paired sample t-test obtained a p-value of 0.001, while hypothesis II test using a paired sample t-test obtained a p-value of <0.001. Hypothesis III test using an independent sample t-test obtained a p-value of 0.042 (p<0.005). Conclusion: Progressive muscle relaxation combined with exercise for the elderly has an effect on lowering blood pressure in elderly people with hypertension. Both interventions can be used to lower blood pressure in the elderly.